2006
DOI: 10.1200/jco.2006.24.18_suppl.9050
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiotherapy in pediatric malignancies

Abstract: 9050 Background: To evaluate the role of palliative radiotherapy in the management of incurable pediatric malignancies. Methods: Records of 40 pediatric patients treated between Jan’ 2003 and Nov’ 2005 were reviewed and analyzed retrospectively. All of theses 40 children received palliative external beam radiotherapy for symptom control. Palliative radiotherapy was given either as single modality or in addition to surgery, chemotherapy and symptom relief drugs. Information recorded for each patient included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…Based on previous reports [ 16 19 ], chemotherapy provides a good palliation of extraocular retinoblastoma, even multi-drug combination chemotherapy was adopted in our department, including vincristine, etoposide/teniposide, carboplatin, and cyclophosphamide, combined with intrathecal injection treatment in each cycle of the chemotherapy. Our results also showed that NSE level in the serum and white blood cell count were significantly reduced after chemo and radiotherapy [ 20 ]. Furthermore, findings of the present study are consistent with Palma et al who reported a significantly improved in treatment with APBSCT [ 21 ], suggesting it play a potential role in the treatment of retinoblastoma.…”
Section: Discussionmentioning
confidence: 52%
“…Based on previous reports [ 16 19 ], chemotherapy provides a good palliation of extraocular retinoblastoma, even multi-drug combination chemotherapy was adopted in our department, including vincristine, etoposide/teniposide, carboplatin, and cyclophosphamide, combined with intrathecal injection treatment in each cycle of the chemotherapy. Our results also showed that NSE level in the serum and white blood cell count were significantly reduced after chemo and radiotherapy [ 20 ]. Furthermore, findings of the present study are consistent with Palma et al who reported a significantly improved in treatment with APBSCT [ 21 ], suggesting it play a potential role in the treatment of retinoblastoma.…”
Section: Discussionmentioning
confidence: 52%
“…While palliative RT is established for adult malignancies, it is less well characterized in the pediatric population. This single‐institution series of children receiving palliative RT for incurable, advanced malignancies contributes to a small but growing set of data in the literature supporting the continued and routine use of palliative RT in the pediatric setting, and provides novel detail on RT‐associated toxicity. In our study, palliative RT was well tolerated in children, and associated with low rates of toxicity and improved or stable symptoms in the majority of cases.…”
Section: Discussionmentioning
confidence: 98%
“…While dose and fractionation schemes for palliative RT have been extensively studied in adults particularly with bone or brain metastases, the optimal dose for palliating disease in pediatric cancer patients has not been well studied. Bone metastases have been studied in several reports of palliative RT in children, but there continues to be limited data to form a consensus recommendation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palliative radiotherapy in children is effective and durable especially when used as part of a palliative care plan. [31][32][33][34] However, knowledge and utilization of pediatric radiotherapy among pediatric oncologists is poor even in HIC. 35 The responsibility of the team is to ensure that each child is assessed according to the best available standards, treated according to All pediatric patients requiring RT should be seen and assessed by the RO in clinic prior to the RT planning appointment.…”
Section: Patients Requiring Palliative Radiotherapymentioning
confidence: 99%